Rady pracownicze w centralach i oddziałach banków — udział pracowników banków w zarządzaniu - Sowiński, Roman (Wydział Prawa i Administracji UAM, 1985)
Participation of workers of head and branch offices of banks in decision making as regards matters concerning their banks is separately regulated according to art. 48 of The Self Government of State Enterprise Workers Act. of September 25, 1981. It was legislated in art. 88 of The Banking Law Act of February 26, 1982 and in the Decree of the Council of Ministers of February 10, on the election of and principles of operation of workers' councils in head and branch offices of banks. This regulation varies from the regulation of self-government of State enterprise Workers on account of its formal character and matter. The differences regard the organizational structure, character and types of competence, forms of activity as well as protection of the workers right to participate in decision making processes. The following questions seem essential: 1. Banking law and the above cited Decree provide only a one type of organ that is a workers' council numbering 9-11 members in the head offices and 3-9 members in the branch offices. 2. Upon regulating competence of workers' councils in the banks, the Decree leaves them only vested with competence to make motions and act within advisory scope. 3. Responsibilty of a bank chairmen or a director before the workers and their organs is not provided. There are consequently no elements manifesting self- -governing character of a bank as an organizational unit and indicating at the workers as a subject to participate in a decisionmaking process in the interrelations between a bank organ and organ of workers' self-government. 4. The regulation of status and operation of workers councils in banks does not include provisions on a protection of labor relation of members of those organs.5. Provisions of Banking Law and of the cited Decree fail to formulate the principle of independence of workers councils of banks from the State administration organs. These and other divergences quoted in the article are convincing on specific features of workers councils in banks as compared with the institution of State enterprise workers self-government regulated in the relevant act. Consequently, provisions of Banking Law and of the Decree of Council of Ministers cannot be recognized as executing art. 48 of the Workers Self-Government Act having of course established that banks are the enterprises within a meaning of both Acts of September 25, 1981. If however we adopt that banks are not the enterprises, then the Banking Law regulation must be recognized as a self-contained source of right of bank workers to participate in decision making regarding those institutions. Apart of formal obstacles, the others can be quoted which prevent recognition of bank workers councils as a form of selfgovernment as in case of enterprises: 1) lack of competence to lay down rules, 2) no possibility for bank workers to participate directly in decision making, 3) no possibility for „self-definition" as e.g. in a form of statute, 4) no independence of bank workers' councils from the State administration 5) impossibility to recognize any bank workers council as an organ representing the whole body of workers, 6) undertaking activity in a result of motions originating from outside. In that state of affairs the participation of workers in banks approaches; a form of consultation. It is resulted by priorities assigned by the legislator to structural and functional elements related to position of bank in the economy, before the recognition of subject status of workers employed in banks
Workers' Councils in head and branch offices of banks — participation of bank workers in management